The Effect of Various Vehicles on the Naproxen Permeability through Rat Skin: A Mechanistic Study by DSC and FT-IR Techniques - Anayatollah Salimi; Najme Hedayatipour; Eskandar Moghimipour (Tabriz University of Medical Sciences, 2016)
Purpose: The purpose of the present investigation was to evaluate the effectiveness of different vehicles on drug permeability and microstructure of intercellular or lipids in SC layer of skin. Methods: Pre-treated skin of rat using some vehicles including Labarac PG ,Transcutol P, tween 80, span 80 and propylene glycol (PG), were mounted on specialized design franz-diffusion cell was used to assess naproxen permeation and parameters such as permeability coefficients and state flux (Jss) were evaluated. Any differences in peak position and also change in symmetric and asymmetric stretching of C-H bond, lipid ester carbonyl stretching in SC, C=O stretching (Amide I) and C-N stretching of keratin (Amide II) absorbance using Fourier transform infrared spectroscopy (FTIR) were considered to investigate the enhancing mechanism. DSC method was utilized to compare their mean transition temperature (Tm) and enthalpies (ΔH). Results: Steady-state flux (Jss), permeability coefficient (Kp) and diffusion coefficient (D) were significantly (p<0.05) increased by using their span80 showed the biggest enhancement ratio (ERflux) and Transcutol P, Labrafac PG, Tween 80 and Propylene glycol were at the next levels. In comprised to hydrated rat skin the maximum increase in diffusion coefficient was for Tween 80(p<0.05), Lipid fluidization, lipid disruption structure and the irreversible denaturation of proteins in the SC layer of skin by span 80, Tween 80, Labrafac PG, Transcutol P and propylene glycol, were indicated by FT-IR and DSC techniques. Conclusion: It is concluded that naproxen permeation through rat skin may be facilitated by utilizing the vehicle systems. Lipid fluidization and lipid extraction are among suggested mechanisms.